EFFECTIVENESS OF ROLE PLAY ON ATTITUDE TOWARDS MENTAL ILLNESS AMONG ADOLESCENTS - G. Balamurugan; M. Vijayarani (Indian Journal of Psychiatric Nursing)
The lack of substantial knowledge concerning mental disorders is conductive to emerging of stereotypes and discrimination against the mentally ill. A pre-experimental study was conducted to assess the effectiveness of Role-play on attitude towards mental illness among adolescents studying in a selected high school at, Bettahalasoor, Bangalore, Karnataka, India” with the AimTo find the effectiveness of Role-play on attitude towards mental illness among adolescents. A Socio Demographic tool and attitude scale was used to assess the attitude. Pre-test was conducted followed with 45 min of Role-playwhich was conducted by the IV year BSc Nursing students regarding the attitude towards mental illness. The post test was conducted after 7 days. The results revealed that mean attitude prior to the role-play (66.93+8.765) and after the role-play (73.33+7.545) was statistically significant. (t=3.132, p=0.004). Male adolescents (70.69+10.012) are having higher attitude than female (63.94+6.823) counterparts (t=2.197, p=0.036). Thus the study reveals that role-play is an effective method to change the quality of attitude towards mental illness among adolescents.